Photoalignment in Polysiloxane Liquid‐Crystalline Elastomers with Rearrangeable Networks. Issue 9 (16th February 2021) - Ube, Toru; Tsunoda, Haruna; Kawasaki, Kyohei; Ikeda, Tomiki
Abstract: Molecular alignment in liquid‐crystalline elastomers with polysiloxane backbone is controlled with the aid of photoalignment and exchangeable links to enhance performance as photoactuators. The photoalignment is triggered by trans ‐ cis ‐ trans isomerization of azobenzene moieties, which are introduced at crosslinking points, upon irradiation with linearly polarized UV (LPUV) light under heating. The induced alignment is memorized by rearrangement of network structures through exchange reactions of covalent bonds. When irradiated with LPUV light, freestanding films show bending along with the alignment change in surface regions. Macroscopic shapes are also rememorized by exchange reactions at crosslinks. Combination of photoalignment and network rearrangement allows continuous deformation of freestanding films upon exposure to LPUV light with varying polarization directions. This approach enhances the degree of freedom in alignment control, photoactuation, and reshaping of polysiloxane‐based liquid‐crystalline elastomers, which are feasible as soft actuators. Abstract : Molecular alignment in polysiloxane liquid‐crystalline elastomers is altered and memorized by combination of photoalignment technique and exchangeable link. Upon irradiation with linearly polarized UV light under heating, the alignment of mesogens is changed and rememorized by rearrangement of network structures, leading to reshaping of freestanding films.